Application of demand side management (DSM) as strategic option to reduce energy consumption and cost for commercial building [electronic resource] - Farah Azleen Jamal, 1984- (2012)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2012